Efektivitas pendekatan Problem Based Learning (PBL) dalam peningkatan kemampuan berpikir kritis matematis siswa SMP pada materi perbandingan - Putri, Dinah Hanifah Utami; Rosyana, Tina; Rohaeti, Euis Eti (IKIP Siliwangi, 2024)
This study aims to assess the effectiveness of the Problem Based Learning (PBL) approach in enhancing junior high school students' mathematical critical thinking skills on the topic of ratios. The subjects of the study were students from SMP IT Nur Al Rahman Cihanjuang, divided into two classes. One class, comprising 21 students, served as the experimental group and received instruction through the Problem Based Learning (PBL) approach, while the other class, also consisting of 21 students, served as the control group and received conventional instruction. The instruments used included interview sheets, documentation studies, student response questionnaires, observation sheets, and a test of mathematical critical thinking skills with 5 essay questions. The data obtained from the pretest and posttest were analyzed using inferential and descriptive statistics. The study's findings indicated that the Problem Based Learning (PBL) approach was more effective in improving the mathematical critical thinking skills of junior high school students on the topic of ratios compared to conventional teaching methods. Consequently, there was an improvement in the mathematical critical thinking skills of students using the PBL approach compared to those using conventional teaching methods.